Hepatitis B Virus (HBV) and S-Escape Mutants: From the Beginning until Now - Perazzo, Priscila (2015)
Despite of the progress made in vaccine and antiviral therapy development, hepatitis B virus (HBV) infection remains a major health care problem. More than 240 million people are chronically infected worldwide showing differences in the severity of liver disease, clinical outcome and response to immune- and antiviral-therapy. Parameters associated with the host immune system (HBV specific T- and/or B-cell repertoires, defective antigen presentation and diminished Th1/Th2 response ratio) and viral factors such as the HBV genotypes and their evolving variants/mutants, have largely contributed to explaining such differences. The unique genomic structure and replication cycle of HBV provide much opportunity for mutations to occur in any of its genes undergoing selection pressures, such as those associated with the host immune system, the hepatitis B vaccine and/or hepatitis B immune globulin and the antiviral therapy with nucleos(t)ide analogues. Firstly, this review describes the current prevalence of S-escape mutants worldwide. Secondly, the clinical implications of such surface gene variants and the impact of universal hepatitis B vaccination on HBV mutations and genotypes are discussed. Finally, the fact that the immune escape process also extends well beyond HBV is addressed.